Caryopteris odorata and its metabolite coumarin attenuate characteristic features of cardiometabolic syndrome in high-refined carbohydrate-high fat-cholesterol-loaded feed-fed diet rats - Mobeen Ghulam Ahmed; Malik Hassan Mehmood; Shumaila Mehdi; Maryam Farrukh (Frontiers Media S.A., 2023)
Caryopteris odorata (D. Don) B.L. Robinson (Verbenaceae family) is an aromaric shrub traditionally used to treat diabetes and related pathologies (diabetic foot ulcer), cancer/tumors, wound healing, and inflammation. It is enriched with flavonoids and phenolics like coumarins, quercetin, gallic acid, coumaric acid, stigmasterol, α-tocopherol, and iridoids. C. odorata has been reported as having α-glucosidase, anti-inflammatory, and anti-oxidant properties. Its effectiveness in preventing cardiometabolic syndrome has not yet been assessed. This study aims to investigate the potential efficacy of C. odorata and coumarin for characteristic features of cardiometabolic syndrome (CMS), including obesity, dyslipidemia, hyperglycemia, insulin resistance, and hypertension by using high-refined carbohydrate-high fat-cholesterol (HRCHFC)-loaded feed-fed rats. Chronic administration of C. odorata and coumarin for 6 weeks revealed a marked attenuation in body and organ weights, with a consistent decline in feed intake compared to HRCHFC diet fed rats. The test materials also caused a significant reduction in the blood pressure (systolic, diastolic, and mean) and heart rate of HRCHFC-diet fed rats. Improved glucose tolerance and insulin sensitivity tests were also observed in test material administered rats compare to only HRCHFC-diet fed rats. C. odorata and coumarin-treated animals produced a marked decline in serum FBG, TC, TG, LFTs, and RFTs, while an increase in serum HDL-C levels was noticed. C. odorata and coumarin also significantly modulated inflammatory biomarkers (TNFα, IL-6), adipokines (leptin, adiponectin, and chemerin), and HMG-CoA reductase levels, indicating prominent anti-inflammatory, cholesterol-lowering, and anti-hyperglycemic potential. Administration of C. odorata and coumarin exhibited a marked improvement in oxidative stress markers (CAT, SOD, and MDA). Histopathological analysis of liver, heart, kidney, pancreas, aorta, and fat tissues showed a revival of normal tissue architecture in C. odorata and coumarin-treated rats compared to only HRCHFC-diet fed rats. These results suggest that C. odorata and coumarin possess beneficial effects against the characteristic features of CMS (obesity, insulin resistance, hypertension, and dyslipidemia) in HRCHFC feed-administered rats. These effects were possibly mediated through improved adipokines, glucose tolerance, and insulin sensitivity, the attenuation of HMG-CoA reductase and inflammatory biomarkers, and modulated oxidative stress biomarkers. This study thus demonstrates a rationale for the therapeutic potential of C. odorata and coumarin in CMS.